Submersion Injuries and the Cost of Injury Associated with Drowning Events in the United States, 2006–2015. - Hansen, Regina M.; Agana-Norman, Denny Fe G.; Hufton, Amie; Hansen, Michael A. (Journal of Community Health, 2024)
Introduction: The World Health Organization has reported submersion injuries as the third most common cause of death due to unintentional injury in the world. Greater detail in the rates, risk factors, and healthcare associated costs of submersion injuries could be instrumental in demonstrating the need for further funding and intervention. Methods: The study was a cross-sectional analysis of a nationally representative dataset of inpatient and emergency department (ED) encounters between 2006 and 2015 in the United States (US). Healthcare utilization costs were provided within the datasets and adjusted to reflect actual charges and provider fees. Lastly, the final cost values were adjusted to the 2020 US dollar (USD) and summarized using a log adjusted mean. Results: On average, there were 11,873 submersion injuries per year that presented to the ED in the US. Resulting in a rate where approximately 9 out of every 100,000 ED visits were associated with a submersion injury. Slightly more than 6% died in the ED, 24.2% were admitted, and 69.3% were discharged from the ED. In total, annual cost of submersion injuries in the US for ED care is approximately $12.5 million, inpatient care is approximately $27.5 million, and total annual healthcare cost exceeds $40 million. Discussion: While these results only represent a fraction of the total cost associated with submersion injuries, it remains substantial and unchanged over the 10-year study period. Certain demographic groups showed higher rates of injury and disease burden, thus bearing a greater amount of the cost.